Writing Instruction in Secondary Schools: Unraveling Practices and Challenges - Karki, Tirtha (Journal of NELTA Gandaki, 2019)
In a discourse related to teaching writing in second or foreign language classrooms, there is a focus on process writing which seems still new practice in many Nepali classrooms. In this context, this study was conducted to explore secondary level English teachers' practices and challenges of teaching writing. The study adopted qualitative research design. For this, twenty secondary level English teachers from both public and private schools of Sunsari District, Nepal were selected as informants. The data were collected through classroom observation, semi- structured interview and Focused Group Discussion (FGD). First, classroom observation of eight teachers was carried out followed by semi-structured interview. Then, the other twelve teachers were invited for FGD. Analysis of qualitative data uncovered that majority of the teachers adopted product approach to teaching writing with abundant stress on support to students for securing good marks in the final examination. The major challenges revealed behind this situation were large class size, low proficient learners, pressure on course completion, lack of practical training for teachers, and insufficient resources including ICT facility in the classroom contexts.